2012
DOI: 10.4028/www.scientific.net/ddf.332.35
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Nanoceramic Magnesium Ferrite Material Doped with Samarium and Dysprosium for Designing – Microstrip Patch Antenna

Abstract: The novel nano ceramic magnesium ferrite material doped with double lanthanide i.e., Samarium (Sm) and Dysprosium (Dy) showed the n-type semiconductor, was synthesized by sol-gel technique and sintered in a microwave furnace in order to enhance the electrical and magnetic behavior of this material as per the requirement of Microstrip patch antenna. The structural, surface morphological and chemical compositional properties of this material were investigated by X-ray diffraction (XRD), SEM and E-DAX. E-DAX was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…There was a noticeable decrease in electrical resistivity for all samples, i.e., by about two orders of magnitude, in the frequency range of 20 Hz–20 MHz. This is in line with results reported in the literature [ 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 93%
“…There was a noticeable decrease in electrical resistivity for all samples, i.e., by about two orders of magnitude, in the frequency range of 20 Hz–20 MHz. This is in line with results reported in the literature [ 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 93%
“…Using this, they fabricated a microstrip patch antenna, which showed a voltage standing wave ratio of 1.66 dB, a gain of 5.73 dB, and an antenna efficiency of 69.82 at a resonant frequency of 14.9 GHz. 8 Wang et al reported the dielectric characteristics of Mg 2 SiO 4 –Li 2 TiO 3 –LiF ceramics with the addition of CaTiO 3 synthesized using the solid-state reaction. They claimed the enhanced quality factor was due to the increased relative density of the prepared composite.…”
Section: Introductionmentioning
confidence: 99%
“…They measured the dielectric permittivity and observed it from 1.68 to 3.18, with a dielectric loss from 1.12 × 10 –2 to 2.6 × 10 –1 . Using this, they fabricated a microstrip patch antenna, which showed a voltage standing wave ratio of 1.66 dB, a gain of 5.73 dB, and an antenna efficiency of 69.82 at a resonant frequency of 14.9 GHz . Wang et al reported the dielectric characteristics of Mg 2 SiO 4 –Li 2 TiO 3 –LiF ceramics with the addition of CaTiO 3 synthesized using the solid-state reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated patch antenna showed its resonant frequency of 1.575 GHz with VSWR less than 2. Naidu et al (2012) used the magnesium ferrite doped with double Samarium (Sm) and Dysprosium (Dy) for fabricating the microstrip patch antenna. The efficiency of the patch antenna was noticed to be 69.82 at frequency 14.9 GHz, which its gain of about 5.73 dB.…”
Section: Introductionmentioning
confidence: 99%